Identification and characterization of Bacillus subtilis from grass carp (Ctenopharynodon idellus) for use as probiotic additives in aquatic feed. (May 2016) - Guo, Xia; Chen, Dan-Dan; Peng, Kai-Song; Cui, Zheng-Wei; Zhang, Xu-Jie; Li, Shun; Zhang, Yong-An
Abstract: Bacillus subtilis is widely used as probiotic species in aquaculture for water quality control, growth promoting, or immunity enhancing. The aim of this study is to find novel B. subtilis strains from fish as potential probiotics for aquaculture. Eleven B. subtilis isolates derived from the intestinal tract of grass carp were identified by gene sequencing and biochemical tests. These isolates were classified into 4 groups, and the representatives (GC-5, GC-6, GC-21 and GC-22) of each group were further investigated for antibiotic susceptibility, sporulation rate, biofilm formation, activity against pathogenic bacteria, resistance to stress conditions of intestinal tract (high percentage of bile and low pH) and high temperature, which are important for probiotics to be used as feed additives. Additionally, the adhesion properties of the 4 characterized strains were assessed using Caco-2 cell and gut mucus models. The results showed that the 4 strains differed in their capacities to adhere to intestinal epithelial cells and mucus. Furthermore, the strains GC-21 and GC-22 up-regulated the expression levels of IL-10 and TGF-β but down-regulated IL-1β, suggesting their potential anti-inflammatory abilities. Based on physiological properties of the 4 characterized B. subtilis strains, one or more strains may have potential to be used as probiotics in aquaculture. Highlights: Eleven Bacillus subtilis strains were isolated from the intestinal tract of grass carp. Four representative B. subtilis strains had potential to be used as probiotics in aquaculture. The four B. subtilis strains possessed different capacities to adhere to intestinal epithelial cells and mucus. The two B. subtilis strains showed potential anti-inflammatory abilities.